TMTP1-Modified, Tumor Microenvironment Responsive Nanoparticles Co-Deliver Cisplatin and Paclitaxel Prodrugs for Effective Cervical Cancer Therapy - Jiang G (Dove Medical Press, 2021)
Guiying Jiang,1,* Xueqian Wang,1,* Ying Zhou,1 Chenming Zou,2,3 Ling Wang,1 Wei Wang,1 Danya Zhang,1 Hanjie Xu,1 Jie Li,1 Fei Li,1 Danfeng Luo,1 Xiangyi Ma,1 Ding Ma,1 Songwei Tan,2 Rui Wei,1 Ling Xi1 1Department of Obstetrics & Gynecology, Tongji Hospital, Tongji Medical College, Huazhong University of Science & Technology, Wuhan, Hubei Province, People’s Republic of China; 2Tongji School of Pharmacy, Tongji Medical College, Huazhong University of Science & Technology, Wuhan, Hubei Province, People’s Republic of China; 3School of Pharmacy, Shanghai Jiao Tong University, Shanghai, People’s Republic of China*These authors contributed equally to this workCorrespondence: Ling Xi; Rui WeiDepartment of Obstetrics & Gynecology, Tongji Hospital, Tongji Medical College, Huazhong University of Science & Technology, Wuhan, Hubei, People’s Republic of ChinaTel/Fax +86 27 83662688Email lxi@tjh.tjmu.edu.cn; weirui2018@tjh.tjmu.edu.cnBackground and Purpose: Cisplatin–paclitaxel (TP) combination chemotherapy as the first-line therapy for numerous cancers is hindered by its inadequate accumulation in tumors and severe side effects resulting from non-specific distribution. The aim of this study is to explore whether TMTP1-modified, cisplatin and paclitaxel prodrugs co-loaded nanodrug could improve cervical cancer chemotherapy and relieve its side effects through active and passive tumor targeting accumulation and controlled drug release.Methods: TDNP, with capacities of active targeting for tumors and controlled drug release, was prepared to co-deliver cisplatin and paclitaxel prodrugs. The characteristics were investigated, including the diameter, surface zeta potential, stability and tumor microenvironment (TME) dependent drug release profiles. Cellular uptake, cytotoxicity, drug accumulation in tumors, antitumor effects and safety analysis were evaluated in vitro and in vivo.Results: The oxidized cisplatin and the paclitaxel linked to the polymer achieved a high loading effciency of over 80% and TME-dependent sustained drug release. Moreover, TMTP1 modification enhanced cellular uptake of TDNP and further improved the cytotoxicity of TDNP in vitro. In vivo, TDNP showed an extended blood circulation and increased accumulation in SiHa xenograft models with the aid of TMTP1. More importantly, TDNP controlled tumor growth without life-threatening side effects.Conclusion: Our study provided a novel TP co-delivery platform for targeted chemotherapy of cervical cancer, which was promising to improve the therapeutic effcacy of TP and may also have application in other tumors.Keywords: TME-responsive, targeted co-delivery, combined chemotherapy, cervical cancer